2006
DOI: 10.1021/ja0657253
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Phase Single Quantum Dot Fluorescence Resonance Energy Transfer

Abstract: We present a single particle fluorescence resonance energy transfer (spFRET) study of freely diffusing self-assembled quantum dot (QD) bioconjugate sensors, composed of CdSe-ZnS core-shell QD donors surrounded by dye-labeled protein acceptors. We first show that there is direct correlation between single particle and ensemble FRET measurements in terms of derived FRET efficiencies and donor-acceptor separation distances. We also find that, in addition to increased sensitivity, spFRET provides information about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
373
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 267 publications
(386 citation statements)
references
References 36 publications
12
373
0
1
Order By: Relevance
“…Although a noncovalent conjugation strategy is used here, the ratio of His 6 peptide and thus acceptor DNA acceptor per QD is also easily controlled through the molar ratio added for self-assembly with the QD as repeatedly demonstrated in Refs. [1,2,6,7,11,13,14,21,23] and discussed in detail in references [13,21,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a noncovalent conjugation strategy is used here, the ratio of His 6 peptide and thus acceptor DNA acceptor per QD is also easily controlled through the molar ratio added for self-assembly with the QD as repeatedly demonstrated in Refs. [1,2,6,7,11,13,14,21,23] and discussed in detail in references [13,21,23].…”
Section: Discussionmentioning
confidence: 99%
“…The FRET analysis also accounted for the contribution and any deviation due to Poisson distribution effects on low valence during the selfassembly process as described in Ref. [13,21,23]. …”
Section: Fluorescence Resonance Energy Transfer Analysismentioning
confidence: 99%
“…adenovirus knob protein to small Au clusters (Hainfeld et al 1999), the enzyme glutathione S-transferase (Gupta et al 2008) to quantum dots or by direct binding of the polyhistidine tag to the Zn-containing inorganic surface of CdSe/ZnS quantum dots as discussed before, e.g. for maltose binding protein (Mattoussi et al 2000;Pons et al 2006a) or fluorescent proteins (Dennis & Bao 2008).…”
Section: (Iii) Peptides Proteins Enzymes and Antibodiesmentioning
confidence: 99%
“…However, in contrast to what is mentioned in literature they observed a decrease in avidity when more than 3 proteins were coupled to a single QD. [42] studied the distribution of histidine (His n )-tagged proteins per QD in a solution of QD-protein conjugates with a given nominal protein-to-QD ratio below saturation of the QD surface. They confirmed that in this situation the process follows a Poisson distribution.…”
Section: Packing Of Biomolecules On Qdsmentioning
confidence: 99%
“…gel electrophoresis). When the average conjugate valence exceeds 4 biomolecules per QD the effect of the Poisson distribution is minimized and can be neglected [42,43].…”
Section: Packing Of Biomolecules On Qdsmentioning
confidence: 99%